THE HIGHER SCHOOL LECTURE IN THE CONTEXT OF MODERN EDUCATIONAL PROCESSES - V. I. Zagvyazinsky (Russian State Vocational Pedagogical University, 2015)
The current situation in the higher education requires both the extensive implementation of the new information and communications technologies and transformation of traditional forms and ways of teaching. The author emphasizes the vital necessity of redefining the types, functions, and place of the university lecture in educational process along with the related potentials and advantages. While the mere informative outcome of the lecture is losing its position, the functions related to adjustment, methodology, meaning-building, personal development and moral upbringing are likely to get additional meaning and importance. The author demonstrates the advantages of face-to-face communication between a lecturer and a student; the special emphasis is on the problem-setting lectures implementing the interactive techniques and methods. According to the author, the optimum educational methods and technologies require both the unity and integrity of traditional and modern approaches. The rejection of approbated and recognized methods of interpersonal face-to-face communications can generate the technocratic graduates with a selfish attitude to professional activity and lack of individuality.